Exploring protonation and deprotonation effects with Auger electron spectroscopy - Kryzhevoi, Nikolai V.; Cederbaum, Lorenz S. (The journal of physical chemistry letters, 2012)
Auger electron spectroscopy is demonstrated to be a very efficient tool to probe alterations in local chemical environment due to changes in protonation states. We show that electronic and geometric structure changes induced by protonation or deprotonation are well reflected in Auger spectra through characteristic chemical shifts and spectral shape variations. We also present evidence that Auger spectra are sensitive to relative concentrations of compounds in different protonation states. Special attention is paid to the high kinetic energy spectral regions that exhibit remarkable features resulting from core ICD-like transitions in normal species and Auger transitions in deprotonated fragments. The latter contribution was so far ignored when explaining Auger spectra of species embedded in the environment. This contribution should be reconsidered, taking into account the recently discovered possibility of ultrafast dissociation of core-ionized hydrogen-bonded systems in media.
Gesehen am 26.10.2018